Second law of thermodynamics for relativistic fluids formulated with relative entropy - Dowling, Neil; Flörchinger, Stefan; Haas, Tobias (Physical review, 2020)
The second law of thermodynamics is discussed and reformulated from a quantum information theoretic perspective for open quantum systems using relative entropy. Specifically, the relative entropy of a quantum state with respect to equilibrium states is considered and its monotonicity property with respect to an open quantum system evolution is used to obtain second lawlike inequalities. We discuss this first for generic quantum systems in contact with a thermal bath and subsequently turn to a formulation suitable for the description of local dynamics in a relativistic quantum field theory. A local version of the second law similar to the one used in relativistic fluid dynamics can be formulated with relative entropy or even relative entanglement entropy in a space-time region bounded by two light cones. We also give an outlook toward isolated quantum field theories and discuss the role of entanglement for relativistic fluid dynamics.
Gesehen am 04.12.2020